PENGARUH BRAND IMAGE DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK MAKE OVER DI KOTA KENDARI - Dzakirah, Farah; Nasrul, Nasrul; Sinarwaty, Sinarwaty (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo)
This research was aimed for knowing: (1) the influence of brand image on purchase decision of make over cosmetics in kendari, (2) the influence of celebrity endorser on purchase decision of make over cosmetics in kendari, (3) the influence of brand image and celebrity endorser on purchase decision of make over cosmetics in Kendari.This research used quantitative approach by applying survey method. Sample of this research is 100 respondents in Kendari and the data was collected through questionnaire with Purposive Sampling technique. The data analysis technique used in this research to answer the hypothesis is double linear regression.Â The result of this research shows that: (1) brand image has positive and significant impact on purchase decision, (2) celebrity endorser has positive impact on purchase decision, (3) brand image and celebrity endorser simultaneously has a positive and significant impact on buying decision toward purchase decision.